Comparative Analysis of Steganography for Coloured Images - Suri, Shrutika; Joshi, Himani; Mincoha, Vishakha; Tyagi, Akash (International Journal of Computer Sciences and Engineering, 2014)
Information security has become a major cause of concern because intruders are concerned with reading the information. It is because of electronic dropping security is under threat. This paper deals with the comparative analysis of steganography over coloured images. ï¿½Steganographyï¿½ is a greek word which means ï¿½hidden writingï¿½. It is the art of hiding the secret message within a image. The goal of steganography is to avoid drawing suspicious to transmission of hidden message. It serves a better way of securing message than cryptography which provide security to content of message and not the existence. Original message is being hidden within a carrier such that the changes occurred in carrier are not observed. The hidden message in carrier is difficult to detect without retrieval. Different techniques are described in this paper for steganography over coloured images. One of them is spatial steganography. In this technique some bits in the image pixel is used for hiding data. Second technique is Transform Domain Technique which is a more complex way of hiding information in an image. Using Distortion technique, a stego object is created by applying a sequence of modifications to the cover image. The message is encoded at pseudo-randomly chosen pixels. Masking and Filtering technique embed the information in the more significant areas than just hiding it into the noise level. The hidden message is more integral to the cover image. Steganography is efficient, simple and decreases the degree of attack on secret information and improve image quality.